DOE-Based Investigation of Microstructural Factors Influencing Residual Stress in Aluminum Alloys - Nawon Kwak; Eunkyung Lee (Metals, 2025)
Residual stresses generated during the casting process significantly affect the reliability of the final product, making accurate prediction and analysis of these stresses crucial. In particular, to minimize the difference between simulation results and actual measurements, it is essential to develop predictive simulations that incorporate microstructural characteristics. Therefore, in this study, residual stress prediction simulations were conducted for aluminum components manufactured by high-pressure die casting (HPDC), and measurement locations were selected based on the simulation results. Subsequently, the microstructural characteristics at each location (Si and intermetallic compounds) were quantitatively analyzed, and significant factors affecting residual stress were identified through design of experiments (DOE). As a result, Si sphericity (p-value ≤ 0.05) was observed to be the most significant factor among Si area fraction, IMC area fraction, and Si sphericity, and the residual stress and Si sphericity showed a positive interaction due to the rapid cooling rate and inhomogeneous microstructure distribution. Furthermore, the study demonstrated the effectiveness of DOE in clearly distinguishing the significance of variables with strong interdependencies.